To find the terms of the sequence described by the rule \( A(n) = -4 + (n - 1)(6) \), we can plug in the values of \( n \) for the second, fourth, and eleventh terms.
-
Finding \( A(2) \): \[ A(2) = -4 + (2 - 1)(6) \] \[ = -4 + (1)(6) \] \[ = -4 + 6 \] \[ = 2 \]
-
Finding \( A(4) \): \[ A(4) = -4 + (4 - 1)(6) \] \[ = -4 + (3)(6) \] \[ = -4 + 18 \] \[ = 14 \]
-
Finding \( A(11) \): \[ A(11) = -4 + (11 - 1)(6) \] \[ = -4 + (10)(6) \] \[ = -4 + 60 \] \[ = 56 \]
Summary of Results:
- \( A(2) = 2 \)
- \( A(4) = 14 \)
- \( A(11) = 56 \)
So the values are:
- \( A(2) = 2 \)
- \( A(4) = 14 \)
- \( A(11) = 56 \)